Extreme teaming lessons in complex, cross-sector leadership - Edmondson, Amy C (United Kingdom Emerald Publishing, 2017)
Today's global enterprises increasingly involve collaborative work by teams of experts operating across different professions, organizations, and industries. Extreme Teaming provides new insights into the world of complex, cross industry projects and the ways they must be managed.
Includes bibliographical references (pages 145-192) and index
Keywords: Teams in the workplace